The Antarctic Treaty System - Creek, Alan (University of Canterbury, 2001)
This review examines issues of international law concerning Antarctica. The primary legal regime discussed is the Antarctic Treaty System as this by far the main area Of international law that impacts upon Antarctica. Specific themes discussed are: • Enforceability: Can the Antarctic Treaty System or any other international agreement be usefully enforced? • Durability: Will the treaty system survive the next 50 years? , the next 100? What future events may destroy it? Governance: Ihe current treaty system is independent of the United Nations. What are the consequences of this? Is this a desirable, or sustainable, state of affairs? Conflict: What conflict does or may occur between the ATS and other recognised international law? What about Other regulation such as that practised by IXATO? With regard to the latter, we already have well established international law regarding the 'high seas'. It is likely that there are, or will be, areas where this conflicts with the provisions of the ATS? This review examines issues of international law concerning Antarctica. The primary legal regime discussed is the Antarctic Treaty System as this by far the main area Of international law that impacts upon Antarctica. Specific themes discussed are: • Enforceability: Can the Antarctic Treaty System or any other international agreement be usefully enforced? • Durability: Will the treaty system survive the next 50 years? , the next 100? What future events may destroy it? Governance: Ihe current treaty system is independent of the United Nations. What are the consequences of this? Is this a desirable, or sustainable, state of affairs? Conflict: What conflict does or may occur between the ATS and other recognised international law? What about Other regulation such as that practised by IXATO? With regard to the latter, we already have well established international law regarding the 'high seas'. It is likely that there are, or will be, areas where this conflicts with the provisions of the ATS?